Hubungan Komunikasi terhadap Produktivitas Kerja Karyawan - Rahmat Hidayat; Uliya Hasanah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This study aims to indentify and analyze the relationship between verbal and nonverbal communication on the productivity of employees crimes. The data used in this study are primery data obtined from the quesionnaire. Total sample of 35 employees using multiple correlation method. Analysis technique is a method of multiple correlation analysis, and hypotesis testing using descriptive analysis with the determination range, t test, and F test results showed verbal communication and nonverbal communication has a positive and significant relationship of employees productivity.